The Influence of Digital Display Methods on User Interaction Experience: A Case Study of Stone Carvings in Southern Dynasties Mausoleums - Zhenya Zhu; Lulu Wang; Fauzi Naeim (Ilmu Inovasi Nusantara, 2026)
This study addresses the growing challenge of optimizing user interaction experiences in the digital dissemination of cultural heritage, particularly in the presentation of stone carvings from Southern Dynasties mausoleums. Despite the increasing use of digital media, conventional text-and-image displays often fail to fully engage users and convey the richness of historical artifacts. Therefore, this study aims to examine the influence of different digital display methods on user interaction experience and to identify more effective strategies for enhancing audience engagement. A quantitative research design was employed by developing two types of digital display materials: conventional text-and-image displays and enhanced interactive displays. Data were collected via questionnaire surveys distributed to 110 participants, yielding 101 valid responses. Participants were divided into two groups: Group A (51 participants) experienced the conventional display, while Group B (50 participants) interacted with the enhanced display. The study measured five key dimensions: clarity, engagement, satisfaction, willingness to continue browsing, and sharing intention. Data analysis included descriptive statistics, independent sample t-tests, correlation analysis, and regression analysis. The findings reveal that the enhanced interactive display significantly outperformed the conventional display across all five dimensions. Furthermore, interaction experience demonstrated a strong positive predictive effect on both willingness to continue browsing and sharing intention. These results imply that effective digital dissemination of cultural heritage should prioritize information layering, detailed visualization, and interactive guidance. This study contributes practical insights for designing engaging digital heritage displays and offers a valuable reference for future research on cultural heritage digitalization